Penamaan Desa di Kabupaten Musi Banyuasin dalam Persepsi Toponimi Terestrial - Rahmat Muhidin (Kantor Bahasa Lampung, 2020)
This study aims to describe the village naming language in Musi Banyuasin Regency based on terrestrial toponymy perceptions. The problem of this research is why the people of Musi Banyuasin Regency in naming an area such as a village or village are related to the empirical experiences they have experienced and what is the background to the mindset of the people of Musi Banyuasin Regency in naming the village in their environment.The results of the study show that the naming language of villages in Musi Banyuasin Regency based on terrestrial toponym perception refers to marine (maritime) resources. Village naming tends to refer to (1) people's names; (2) names of plants; (3) elements of geographical name: (a) coral; (b) kebon; (c) quality; (d) weeds; (e) estuary; (f) island; (g) overseas; (h) swamp; (i) jungle; (j) land; (k) chamfer; (l) telang; (m) river; (n) support; (o) cliffs; (p) bay; (q) names originating from the name of the cape; (r) name of embankment; (s) relating to the base; (t) use the word lubuk; and (u) related to hope. AbstrakPenelitian ini bertujuan mendeskripsikan bahasa penamaan desa di Kabupaten Musi Banyuasin berdasarkan persepsi toponimi terestrial. Masalah penelitian ini adalah mengapa masyarakat Kabupaten Musi Banyuasin dalam menamai suatu wilayah seperti kampung atau desa berkaitan dengan pengalaman empiris yang dialaminya dan apa sajakah yang melatarbelakangi pola pikir masyarakat Kabupaten Musi Banyuasin dalam menamai desa di lingkungannya. Hasil kajian menunjukkan bahasa penamaan desa di Kabupaten Musi Banyuasin berdasarkan persepsi toponimi terestrial mengacu pada sumber daya marine (maritim). Penamaan desa cenderung mengacu pada (1) nama orang; (2) nama tumbuhan; (3) unsur nama geografis: (a) karang; (b) kebon; (c) kuala; (d) lalang; (e) muara; (f) pulau; (g) rantau; (h) rawa; (i) rimba; (j) tanah; (k) talang; (l) telang; (m) sungai; (n) upang; (o) tebing; (p) teluk; (q) nama yang berasal dari nama tanjung; (r) nama pematang; (s) berhubungan dengan pangkalan; (t) menggunakan kata lubuk; dan (u) berhubungan dengan harapan.